Parenting Relationship and Learning Discipline for Children Aged 4-5 Years - Amalia, Kurnia Rizky; Iriyanto, Tomas; Astuti, Wuri (Green Publisher Indonesia, 2025)
Parenting styles play an important role in shaping the learning discipline of young children. However, differences in discipline levels among children aged 4–5 years persist, influenced by varying parenting styles. The researcher is interested in this topic because early childhood education serves as a foundation for children’s academic and character development. This study aims to examine whether there is a relationship between parenting styles and the learning discipline of children aged 4–5 years at TK Permata Iman 2 Malang. This research uses a quantitative approach with a correlational research design. Data was collected through questionnaires distributed to the parents of students at TK Permata Iman 2 Malang. The data analysis techniques employed include descriptive analysis and classical assumption testing, such as normality testing. The results showed a correlation coefficient of rx = 0.782, indicating a